Modern Epistemology against Analytic Philosophy: A Reply - McCloskey, Donald N. (Journal of Economic Literature, 1995)
Uskali Maki read three books by McCloskey on the "rhetoric of economics" with sympathy. But he wants McCloskey to choose between a coherence and a correspondence theory of truth. McCloskey notes in reply that modern epistemology - by contrast with the analytic philosophy circa 1955 that many philosophers of economics espouse - rejects the choice. Modern epistemology would say that economic scientists argue in many legitimate ways, governed by ethics. In brief, as Maki agrees, economics has a rhetoric. Rhetoric is a better guide than 1955-style analytic philosophy.